Exploring the Impact of Organisational Values on Nurses’ Resilience Levels: A Mixed Methods Study - Cooper, Alannah Louise (Curtin University, 2021)
The research consisted of a concept analysis to define nurse resilience, an integrative review to critically appraise research that has investigated nurse resilience, and a mixed-methods study to investigate the impact of organisational values on nurse resilience. Organisational values have the potential to positively impact resilience, when nurses agree with those values and feel the values are upheld by the organisation. Perceived failures by the organisation to uphold the values negatively impact resilience.